Social Historical Analysis of Legal Clinics. Balance of the UPTC Legal Clinic in the Labour Area 2018-2019 - Zipa Vargas, Nury Johana; Cepeda Villar, Luis Carlos; Fonseca , Yair Leonardo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This research article using an inductive method with a quantitative approach carried out a historical social analysis of legal clinics, both internationally and from a national point of view. From the above, it was established as the main research objective to make a detailed and truthful study based on concrete and real information of the effectiveness of the legal clinic Armando Suescún Monroy from the Pedagogical and Technological University of Colombia, in regard to access to justice, particularly in the area of ​​labour law, because it is of public interest and vital importance for vulnerable populations within the framework of their competence. The results obtained in this research have been conclusive and cause for reflection. Most users after a long lapse withdraw their claims, the processes that enter the jurisdiction are few, which leads to the conclusion that the function of the legal clinic is being left in a simple formality.